ISOLASI DAN KARAKTERISASI BAKTERI ENDOFIT PENGHASIL ENZIM KATALASE DARI DAUN BUASBUAS (PREMNA PUBESCENS BLUME) - Pulungan, Ahmad Shafwan S.; Tumangger, Diana Erawaty (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2018)
This research aims to determine the presence of endophytic bacteria producing catalase enzyme in Buasbuas (Premna pubescens Blume) leaves and how endophytic bacteria producing catalase enzym characteristics of the Buasbuas (Premna pubescens Blume) leaves. This research was conducted with several characterization stages: macroscopic characterization (morphology), microscopic characterization (gram staining) and catalase test. Data analysis technique used is descriptive. The isolation result there are 5 isolates of endophytic bacteria and 3 isolates which have potential to produce catalase enzyme.